A Characterization of E-Benson Proper Efficiency via Nonlinear Scalarization in Vector Optimization - Ke Quan Zhao; Yuan Mei Xia; Hui Guo (Journal of Applied Mathematics)
A class of vector optimization problems is considered and a characterization of E-Benson proper efficiency is obtained by using a nonlinear scalarization function proposed by Göpfert et al. Some examples are given to illustrate the main results.